Preparation method of titanium series lithium ion sieve

By using potassium acetate and metatitanic acid to prepare the titanium lithium ion sieve precursor and elution of hydrochloric acid, the problems of high cost and low adsorption capacity of titanium lithium ion sieve are solved, and high adsorption capacity and stable cycling performance are achieved. Suitable for industrial production.

CN116196882BActive Publication Date: 2025-02-11BEIJING HUATEYUAN TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310380471.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-02-11
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

The industrial production cost of titanium lithium ion sieves is high, the adsorption capacity is low, and the adsorption rate is slow.

Method used

Potassium acetate was used as the potassium source, and beating with metatitanate, dried, and roasted at high temperature to prepare a potassium titanate precursor, and eluted through hydrochloric acid eluent to obtain H2TiO3.

Benefits of technology

Under the condition that the selectivity of lithium ions does not decrease, the layer spacing is widened, the adsorption capacity and circulation performance are improved, and the synthesis cost is reduced. It is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116196882B_ABST
    Figure CN116196882B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method of a titanium-based lithium ion sieve, which belongs to the technical field of ion sieves. Potassium acetate is used as a potassium source, and the potassium ion sieve is slurried together with metatitanic acid, dried, and calcined at high temperature to prepare a potassium metatitanate precursor; a certain mass of potassium metatitanate precursor is taken, and hydrochloric acid eluent is added for elution, and hydrochloric acid solution is added during the elution process to keep the pH value of the slurry between 1.3-2.0; acid addition is stopped after the pH of the slurry remains stable; the obtained slurry is centrifuged and washed, and the obtained solid is dried and crushed to obtain H2TiO3. The present invention replaces the lithium source with potassium salt, and the selectivity of the synthesized lithium ion sieve for lithium ions does not decrease. Under the condition of ensuring that the selectivity does not decrease, the interlayer spacing is appropriately widened, the adsorption capacity is large, the cycle performance is stable, the synthesis cost is reduced, and it is suitable for industrial production; the problems of high preparation cost, low adsorption capacity and slow adsorption rate of titanium-based lithium adsorbent are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion sieves, and in particular to a method for preparing a titanium-based lithium ion sieve with high adsorption capacity and low cost. Background Art

[0002] As the lightest metal element in nature, lithium has high utilization value and a wide range of applications due to its excellent physical and chemical properties. Lithium and its compounds are widely used in chemical industry, glass, ceramics, aerospace, new energy and other fields, making the development and utilization of lithium resources a hot topic.

[0003] There are two main methods for synthesizing ion sieve precursors, solid phase method and liquid phase method. The high temperature solid phase method is one of the most commonly used methods for preparing ion sieve precursors. It mainly involves allowing fusible and easily decomposed salts to undergo solid phase reactions at high temperatures to generate oxides. The two salts of different ions separate, melt, and fuse at high temperatures, and continuously react with each other to form powders with small particle sizes. After synthesizing the required powder, the ion sieve is prepared by the adsorption method. The adsorption method has the characteristics of high selectivity, ability to handle brine with low lithium content, and ability to achieve clean production. It also has a simple process and high recovery rate, making it very suitable for extracting lithium from salt lake water.

[0004] Titanium-based lithium ion sieve adsorbent is an adsorbent material with high selectivity for lithium ions. The synthesis of titanium-based lithium ion sieve generally uses lithium source (containing lithium compounds) and titanium source (containing titanium compounds) as raw materials. However, lithium salts are expensive, resulting in too high an industrial production cost of titanium-based lithium ion sieve. Therefore, it is necessary to adjust the raw materials to prepare an adsorbent with low cost, high adsorption, low dissolution loss, and high cycle performance. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a titanium-based lithium ion sieve with high adsorption capacity and low cost, so as to solve at least one technical problem existing in the above-mentioned background technology.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a titanium-based lithium ion sieve, comprising:

[0008] Potassium acetate is used as a potassium source, and is slurried together with metatitanic acid, dried, and calcined at high temperature to prepare a potassium metatitanate precursor;

[0009] Take a certain mass of potassium metatitanate precursor, add hydrochloric acid eluent for elution, and add hydrochloric acid solution during the elution process to keep the pH value of the slurry between 1.3-2.0;

[0010] Stop adding acid after the pH of the slurry remains stable;

[0011] The obtained slurry is centrifuged and washed, and the obtained solid is dried and crushed to obtain H2TiO3.

[0012] Preferably, titanic acid and anatase TiO2 are added to a potassium acetate solution, and then PEG200 is added and mixed thoroughly, subjected to ultrasonic treatment in a water bath, dried, ground, and calcined to obtain K2Ti6O 13 Precursor.

[0013] Preferably, 50-100 g of potassium acetate is added to 200 ml of deionized water and stirred at room temperature until dissolved to obtain a potassium acetate solution.

[0014] Preferably, 110-240 g of metatitanic acid and 45-50 g of anatase TiO2 are added to the potassium acetate solution.

[0015] Preferably, the mass of PEG200 added is 4-10 g.

[0016] Preferably, ultrasonic treatment is performed at a water temperature of 50-60° C. for 20-30 min, and drying is performed in an oven at 110-130° C. for 6 h-10 h. After sufficient drying, the sample is taken out and transferred into a crucible for grinding.

[0017] Preferably, after grinding, the mixture is transferred to a muffle furnace and heated to 500-650°C for calcination at a heating rate of 2-10°C / min, and then heated to 700-900°C for calcination for 4-8h to obtain K2Ti6O with high specific surface area, large adsorption capacity and high selectivity. 13 Precursor.

[0018] Preferably, a certain mass of potassium metatitanate precursor is taken, 0.05-0.1 mol / L of hydrochloric acid eluent is added, the feed ratio is maintained at 10-20 g / L, and the product is eluted by shaking at 50-60° C. for 1-2 h.

[0019] Preferably, 0.5-2 mol / L hydrochloric acid solution is added during the elution process to keep the pH value of the slurry between 1.3-2.0, and the acid solution is changed twice in the middle to prevent K + If the concentration is too high, back absorption will occur.

[0020] Preferably, the acid addition is stopped after the pH of the slurry remains stable, the obtained slurry is centrifuged and washed 4-5 times, and the obtained solid is dried in an oven at 50-60°C and crushed to obtain H2TiO3.

[0021] The invention has the following beneficial effects: potassium salt is used to replace the lithium source, the selectivity of the synthesized lithium ion sieve for lithium ions does not decrease, and under the condition of ensuring that the selectivity does not decrease, the interlayer spacing is appropriately widened, the adsorption capacity is large, the cycle performance is stable, the synthesis cost is reduced, and it is suitable for industrial production; the problems of high preparation cost, low adsorption capacity and slow adsorption rate of titanium-based lithium adsorbents are solved.

[0022] Additional advantages of the present invention will be more clearly given in the following description or learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0024] Figure 1 This is a flow chart for preparing the potassium titanate precursor described in an embodiment of the present invention.

[0025] Figure 2 This is the XRD pattern of the precursor obtained in Example 1 of the present invention.

[0026] Figure 3 This is a schematic diagram of electron microscope scanning of the precursor obtained in Example 1 of the present invention.

[0027] Figure 4 is the Li described in Example 1 of the present invention + Schematic diagram of the adsorption rate curve.

[0028] Figure 5 The number of cycles for Li described in Example 1 of the present invention + Schematic diagram of the effect of adsorption amount.

[0029] Figure 6 This is the XRD pattern of the precursor obtained as described in Example 2 of the present invention.

[0030] Figure 7 This is a schematic diagram of electron microscope scanning of the obtained precursor described in Example 2 of the present invention.

[0031] Figure 8 is the Li described in Example 2 of the present invention + Schematic diagram of the adsorption rate curve.

[0032] Fig. 9 The number of cycles for Li described in Example 2 of the present invention + Schematic diagram of the effect of adsorption amount. DETAILED DESCRIPTION

[0033] The embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below by the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.

[0034] Those skilled in the art will understand that unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs.

[0035] It should also be understood that terms, such as those defined in commonly used dictionaries, should be understood to have a meaning consistent with that in the context of the prior art and will not be interpreted in an idealized or overly formal sense unless as defined herein.

[0036] Those skilled in the art will appreciate that, unless otherwise stated, the singular forms "a", "an", "said" and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present invention refers to the presence of the features, integers, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements and / or groups thereof.

[0037] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.

[0038] To facilitate understanding of the present invention, the present invention is further explained below with reference to specific embodiments in conjunction with the accompanying drawings, and the specific embodiments do not constitute a limitation on the embodiments of the present invention.

[0039] Those skilled in the art should understand that the drawings are merely schematic diagrams of embodiments, and the components in the drawings are not necessarily necessary for implementing the present invention.

[0040] like Figure 1 As shown, in this embodiment, a method for preparing a titanium-based lithium ion sieve with low cost, high adsorption capacity, high selectivity and high adsorption rate is provided as follows:

[0041] Preparation of titanium-based lithium ion sieve precursor: Potassium acetate is used as a potassium source, and is slurried together with metatitanic acid, dried, and calcined at high temperature to prepare a potassium metatitanate precursor.

[0042] The preparation of the titanium-based lithium ion sieve precursor specifically includes: adding 55-100g of potassium acetate to 200ml of deionized water, stirring at room temperature until dissolved, slowly adding 111-238g of metatitanic acid and 45-50g of anatase TiO2 to the above solution, adding 4-10g of PEG200 and mixing thoroughly, ultrasonically treating at 50-60°C water temperature for 20-30min, drying in an oven at 110-130°C for 6h-10h, taking out the sample after sufficient drying, transferring it to a crucible, grinding it thoroughly, transferring it to a muffle furnace, and calcining it by programmed temperature increase at a heating rate of 2-10°C / min, first increasing it to 500-650°C, calcining it for 4-8h, and then increasing it to 700-900°C and calcining it for 4-8h, thereby obtaining K2Ti6O with high specific surface area, large adsorption capacity and high selectivity. 13 Precursor.

[0043] Add a certain amount of precursor to a beaker, add 0.05-0.1 mol / L hydrochloric acid eluent, keep the feed ratio at 10-20 g / L, and elute at 50-60 ° C for 1-2 hours. During the process, add 0.5-2 mol / L hydrochloric acid solution to keep the slurry pH between 1.3-2.0. Change the acid solution twice in the middle to prevent K + If the concentration is too high, back absorption will occur. Stop adding acid after the pH of the slurry remains stable. Centrifuge the obtained slurry and wash 4-5 times. The obtained solid is dried in an oven at 50-60°C and crushed to obtain a titanium-based lithium ion sieve of H2TiO3.

[0044] Example 1

[0045] Add 55g of potassium acetate to 200ml of deionized water and stir at room temperature until dissolved. Add 111g of metatitanic acid and 45g of anatase TiO2 to the above solution, add 4g of PEG200 to the beaker containing the sample and mix thoroughly, ultrasonically treat at 50°C water temperature for 20min, and dry in an oven at 110°C for 10h. After sufficient drying, take out the sample, transfer it to a crucible, grind it thoroughly, transfer it to a muffle furnace, and calcine it by programmed temperature increase at a heating rate of 4°C / min to 500°C for 4h, then to 700°C for 8h, cool and grind it, so as to obtain K2Ti6O with high specific surface area, large adsorption capacity and high selectivity. 13 Precursor. The XRD pattern of the precursor obtained in this embodiment is as follows Figure 2 As shown, compared with the standard card PDF #74-0275, the precursor obtained is K2Ti6O 13 Precursor K2Ti6O13 The microscopic morphology of Figure 3 As shown, it can be seen that the obtained precursor is nanoscale particles with uniform particle size distribution.

[0046] Add a certain mass of precursor into a beaker, add 0.05 mol / L hydrochloric acid eluent, keep the feed ratio at 20 g / L, and elute at 50°C for 1h. During the process, add 2 mol / L hydrochloric acid solution to keep the slurry pH value between 1.3-2.0. Change the acid solution twice in the middle to prevent K + If the concentration is too high, back absorption will occur. When the pH of the slurry remains stable, stop adding acid. The obtained slurry is centrifuged and washed 4 times. The obtained solid is dried in an oven at 50°C and then crushed to obtain H2TiO3.

[0047] Li + Adsorption performance test: 1L of laboratory-prepared brine (containing lithium chloride (4.45g), sodium silicate nonahydrate (0.21g), anhydrous sodium sulfate (84.92g), anhydrous sodium carbonate (15.57g), sodium chloride (28.39g), calcium chloride (0.19g), magnesium chloride (8.93g), potassium chloride (12.78g)) was used to test the adsorption performance. 20g of the titanium-based lithium ion sieve in Example 1 was soaked in 1L of laboratory-prepared brine and stirred continuously. A water sample was taken every 20 minutes, and the Li + When the water sample contains Li + When the content no longer changes, the adsorption is in equilibrium. The adsorption rate curve is as follows: Figure 4 As shown, the adsorption reaches equilibrium after 140 min, and the equilibrium adsorption amount is 31 mg / g, which proves that the adsorption capacity of the titanium-based lithium ion sieve is high.

[0048] Take 2g of the lithium adsorbent after adsorption in Case 1, keep the feed ratio at 20g / L, analyze the adsorbed sample, use 0.1 mol / L hydrochloric acid solution as the analytical solution, take samples every half an hour, and test the Li + , K + , Ca 2+ , Na + ,Mg 2+ The content and selectivity data are shown in Table 1. From Table 1 and Table 2, it can be concluded that the lithium adsorbent obtained by replacing the lithium source with potassium salt still has high selectivity.

[0049] Table 1 Ion concentrations of adsorption solution and analytical solution in Experimental Case 1

[0050] element <![CDATA[Li + ]]> <![CDATA[Na + ]]> <![CDATA[K + ]]> <![CDATA[Ca 2+ ]]> <![CDATA[Mg 2+ ]]> Adsorption solution ion concentration mg / L 620.48 38206.30 5513.67 53.29 1866.37 Ion concentration of analytical solution mg / L 576.46 45.61 10.69 33.07 11.71

[0051] Table 2 Ion concentration ratio of analytical solution in experimental case 1

[0052] 30min 60min <![CDATA[Li + / That + ]]> 12.53 12.64 <![CDATA[Li + / K + ]]> 55.86 53.95 <![CDATA[Li + / As 2+ ]]> 15.47 17.43 <![CDATA[Li + / Mg 2+ ]]> 46.33 49.26

[0053] The recycling performance of materials has a great impact on the operating costs of industrial operations. Therefore, the cyclic adsorption performance of lithium ion sieves is explored in experiments such as Figure 5 As shown, the adsorption performance fluctuated in the range of 29.5-31 mg / g after 9 cycles, and there was no sharp decline in the adsorption amount, indicating that the titanium-based lithium ion sieve adsorbent obtained by this experimental method has good cyclability, which ensures that the titanium-based lithium ion sieve can achieve stable operation of the system during actual use.

[0054] Example 2

[0055] 100g of potassium acetate was added to 200ml of deionized water and stirred at room temperature until dissolved. 238g of metatitanic acid and 50g of anatase TiO2 were slowly added to the above solution, 10g of PEG200 was added to the beaker containing the sample and mixed thoroughly, ultrasonically treated at 60°C water temperature for 30min, dried in an oven at 130°C for 6h, and after being fully dried, the sample was taken out and transferred to a crucible. After being fully ground, it was transferred to a muffle furnace and calcined by programmed temperature increase at a rate of 5°C / min, first raised to 650°C, calcined for 8h, and then raised to 900°C for calcination for 4h, cooled, crushed and ground, thereby obtaining K2Ti6O with high specific surface area, large adsorption capacity and high selectivity. 13 Precursor. The XRD pattern of the precursor obtained in Example 2 is as follows Figure 6 As shown, compared with the standard card PDF #74-0275, the precursor obtained is K2Ti6O 13 Precursor K2Ti6O 13 The microscopic morphology of Figure 7 As shown, it can be seen that the obtained precursor is nanoscale particles with uniform particle size distribution.

[0056] Add a certain amount of precursor to a beaker, add 0.1 mol / L hydrochloric acid eluent, keep the feed ratio at 10g / L, stir and elute at 60°C for 2h, add 0.5 mol / L hydrochloric acid solution during the process to keep the slurry pH value between 1.3-2.0, change the acid solution twice in the middle to prevent K + If the concentration is too high, back absorption will occur. When the pH of the slurry remains stable, stop adding acid. The obtained slurry is centrifuged and washed 5 times. The obtained solid is dried in an oven at 60°C and crushed to obtain H2TiO3.

[0057] Li +Adsorption performance test: The adsorption performance was tested using laboratory self-prepared brine. The components and dosages in the self-prepared brine were the same as those in Example 1. 10 g of the lithium adsorbent in Example 1 was soaked in 1 L of laboratory prepared brine and stirred continuously. Water samples were taken every 20 minutes and Li + When the water sample contains Li + When the content no longer changes, the adsorption is in equilibrium. Figure 8 As shown, the adsorption reaches equilibrium after 120 min, and the equilibrium adsorption amount is 35 mg / g, which proves that the adsorption capacity of the titanium-based lithium ion sieve is high.

[0058] Take 2g of the lithium adsorbent after adsorption in Case 2, keep the feed ratio at 10g / L, analyze the adsorbed sample, use 0.1 mol / L hydrochloric acid solution as the analytical solution, take samples every half an hour, and test the Li + , K + , Ca 2+ , Na + ,Mg 2+ The content and selectivity data are shown in Table 3. As can be seen from Table 3 and Table 4, the lithium adsorbent obtained by replacing the lithium source with potassium salt has high selectivity.

[0059] Table 3 Ion concentrations of adsorption solution and analytical solution in Experimental Case 2

[0060] element <![CDATA[Li + ]]> <![CDATA[Na + ]]> <![CDATA[K + ]]> <![CDATA[Ca 2+ ]]> <![CDATA[Mg 2+ ]]> Adsorption stock solution ion concentration mg / L 618.36 38207.49 5514.21 55.24 1863.66 Ion concentration of analytical solution mg / L 332.56 101.98 6.61 20.94 6.72

[0061] Table 4 Ion concentration ratio of analytical solution in experimental case 2

[0062] 30min 60min <![CDATA[Li + / That + ]]> 11.28 11.36 <![CDATA[Li + / K + ]]> 58.43 50.30 <![CDATA[Li + / As 2+ ]]> 13.22 15.88 <![CDATA[Li + / Mg 2+ ]]> 43.85 49.64

[0063] The recycling performance of materials has a great impact on the operating costs of industrial operations. Therefore, the cyclic adsorption performance of lithium ion sieves is explored in experiments such as Fig. 9 As shown, the adsorption performance fluctuated in the range of 34-35.2 mg / g after 9 cycles, and there was no sharp decline in the adsorption amount, indicating that the titanium-based lithium ion sieve adsorbent obtained by this experimental method has good cyclability, which ensures that the titanium-based lithium ion sieve can achieve stable operation of the system during actual use.

[0064] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art without creative work on the basis of the technical solution disclosed in the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a titanium-based lithium ion sieve, characterized in that: include: Potassium acetate is used as a potassium source, and is slurried together with metatitanic acid, dried, and calcined at high temperature to prepare a potassium metatitanate precursor; Take a certain mass of potassium metatitanate precursor, add 0.05-0.1 mol / L hydrochloric acid eluent, keep the feed ratio at 10-20 g / L, and elute at 50-60 ° C for 1-2 hours; during the elution process, add 0.5-2 mol / L hydrochloric acid solution to keep the slurry pH value between 1.3-2.0, and change the acid solution twice in the middle to prevent K + Back-absorption occurs when the concentration is too high; Stop adding acid after the pH of the slurry remains stable; The obtained slurry is centrifuged and washed, and the obtained solid is dried and crushed to obtain H2TiO3.

2. The method for preparing a titanium-based lithium ion sieve according to claim 1, characterized in that: Metatitanic acid and anatase TiO2 were added to potassium acetate solution, and then PEG200 was added and mixed thoroughly, and then subjected to ultrasonic treatment in a water bath, dried, ground, and calcined to obtain K2Ti6O 13 Precursor.

3. The method for preparing a titanium-based lithium ion sieve according to claim 2, characterized in that: Add 50-100 g of potassium acetate into 200 ml of deionized water and stir at room temperature until dissolved to obtain a methyl acetate solution.

4. The method for preparing a titanium-based lithium ion sieve according to claim 3, characterized in that: Add 110-240g of metatitanic acid and 45-50g of anatase TiO2 to the methyl acetate solution.

5. The method for preparing a titanium-based lithium ion sieve according to claim 4, characterized in that: The mass of PEG200 added is 4-10g.

6. The method for preparing the titanium-based lithium ion sieve according to claim 5, characterized in that: Ultrasonic treatment was carried out at 50-60°C water temperature for 20-30 min, and drying was carried out in an oven at 110-130°C for 6h-10h. After sufficient drying, the sample was taken out and transferred to a crucible for grinding.

7. The method for preparing a titanium-based lithium ion sieve according to claim 6, characterized in that: After grinding, transfer to a muffle furnace and heat up and calcine at a rate of 2-10℃ / min. First, heat to 500-650℃ and calcine for 4-8h, then heat to 700-900℃ and calcine for 4-8h to obtain K2Ti6O with high specific surface area, large adsorption capacity and high selectivity. 13 Precursor.

8. The method for preparing a titanium-based lithium ion sieve according to claim 1, characterized in that: When the pH of the slurry remains stable, the acid addition is stopped, the obtained slurry is centrifuged and washed 4-5 times, and the obtained solid is dried in an oven at 50-60°C and crushed to obtain H2TiO3.

Citation Information

Patent Citations

  • Morphology-controllable potassium hexatitanate powder crystal material and low-energy-consumption preparation method thereof

    CN108166051A

  • Synthesis method of lithium extraction adsorbent

    CN110975795A